Evolutionary responses to climate change in a range expanding plant - Macel, Mirka; Dostálek, Tomáš; Esch, Sonja; Bucharová, Anna; van Dam, Nicole M; Tielbörger, Katja; Verhoeven, Koen J F; Münzbergová, Zuzana (Oecologia, 2017)
To understand the biological effects of climate change, it is essential to take into account species' evolutionary responses to their changing environments. Ongoing climate change is resulting in species shifting their geographical distribution ranges poleward. We tested whether a successful range expanding plant has rapidly adapted to the regional conditions in its novel range, and whether adaptation could be driven by herbivores. Furthermore, we investigated if enemy release occurred in the newly colonized areas and whether plant origins differed in herbivore resistance. Plants were cloned and reciprocally transplanted between three experimental sites across the range. Effects of herbivores on plant performance were tested by individually caging plants with either open or closed cages. There was no indication of (regional) adaptation to abiotic conditions. Plants originating from the novel range were always larger than plants from the core distribution at all experimental sites, with or without herbivory. Herbivore damage was highest and not lowest at the experimental sites in the novel range, suggesting no release from enemy impact. Genotypes from the core were more damaged compared to genotypes from newly colonized areas at the most northern site in the novel range, which was dominated by generalist slug herbivory. We also detected subtle shifts in chemical defenses between the plant origins. Genotypes from the novel range had more inducible defenses. Our results suggest that plants that are expanding their range with climate change may evolve increased vigor and altered herbivore resistance in their new range, analogous to invasive plants.
Keywords: biologická evoluce; Biological Evolution; klimatické změny; Herbivory; rostliny; býložravci; Climate Change; Plants